2019
DOI: 10.1177/2150132719843437
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of a 19-Year-Old With Hypertension and Proteinuria: A Case Report

Abstract: A 19-year-old male presented to the clinic and was found to be prehypertensive and have proteinuria on urine testing. He was subsequently diagnosed with focal segmental glomerulosclerosis (FSGS). Initial workup for pediatric hypertension includes urinalysis, chemistry panel, lipid panel, and renal ultrasound. Abnormalities on urinalysis, including proteinuria, hypercholesterolemia, and low serum albumin in children are characteristic of nephrotic disease. FSGS is a type of kidney pathology that often contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…This compares with a 2011 study in Bangladesh in which there were more hypertension events found in the SRNS group than SSNS (p > 0.05) [2] and in line with research in Indonesia 2016 where blood pressure found in the SSNS group was higher than the SRNS group but not statistically meaningful [3]. Another study by Mamesah 2019 found the average systolic and diastolic blood pressure of the SRNS group compared to the SSNS group [9]. Other studies that support our study have a high prevalence of hypertension in the SRNS and SSNS groups where the prevalence of hypertension in different patient populations with SNs ranges from 8% to 59.1% [14].…”
Section: Figure 1: Systolic Blood Pressure Boxplot Chart In Steroid-resistant Nephrotic Syndrome (Ns) and Steroid Sensitive Ns Groupssupporting
confidence: 84%
See 2 more Smart Citations
“…This compares with a 2011 study in Bangladesh in which there were more hypertension events found in the SRNS group than SSNS (p > 0.05) [2] and in line with research in Indonesia 2016 where blood pressure found in the SSNS group was higher than the SRNS group but not statistically meaningful [3]. Another study by Mamesah 2019 found the average systolic and diastolic blood pressure of the SRNS group compared to the SSNS group [9]. Other studies that support our study have a high prevalence of hypertension in the SRNS and SSNS groups where the prevalence of hypertension in different patient populations with SNs ranges from 8% to 59.1% [14].…”
Section: Figure 1: Systolic Blood Pressure Boxplot Chart In Steroid-resistant Nephrotic Syndrome (Ns) and Steroid Sensitive Ns Groupssupporting
confidence: 84%
“…The incidence of hypertension in children is about 20% caused by kidney disease [9]. Hypertension can be found in disease condition or in the course of NS disease due to steroid toxicity [1].…”
Section: Figure 1: Systolic Blood Pressure Boxplot Chart In Steroid-resistant Nephrotic Syndrome (Ns) and Steroid Sensitive Ns Groupsmentioning
confidence: 99%
See 1 more Smart Citation